(untitled) (Journal of the College of Basic Education, 2026)
Hanif Kureishi’s "We’re Not Jews" and Leila Aboulela’s "The Museum" explore the notions of cultural differences and the feelings of otherness which cross-cultural encounter generates. Writing from the British diaspora, both Kureishi and Aboulela have linked these notions with the ambivalent feelings of their characters. How can double-consciousness act as a strategic power of subversion of the British Empire’s claim to homogeneity? The research will answer this question. Moreover, it shows how interracial mixing, which often produces conflicting feelings for whoever displays visible signs of difference such as skin color in the supposedly homogeneous culture of Britain, can motivate some characters to configure themselves as culturally similar to, yet different from, the British . The research underlines the contradictory nature of colonial encounters which can have a dual effect on both the colonizer and the colonized. It highlights the subversive significance of these intersecting experiences in relation to the notion of performativity of culture. It addresses cultural in-betweenness in an attempt to rethink cultural identity and deconstruct the myth of racial homogeneity that the British Empire propagates. The research shows how cultural hybridization is represented by Kureishi and Aboulela as being a disempowering and an empowering experience through applying the theories of community and the deconstruction techniques, which are introduced by Homi Bhabha, Mikhail Bakhtin, and Jean-Luc Nancy, to the selected texts under study.